Ответы и объяснения

2013-04-26T06:52:05+00:00

2х-3y=12 

2х+y= - 4

 

вычитаем из первого второе

-4у=12+4

-4у=16

у=-4

 

подставляем во второе

2х=-4+4

х=0

Лучший Ответ!
2013-04-26T07:01:55+00:00

 2х-3y=12   выразим x  2x=12+3y    x=12:2+3y:2=6+1,5y подставим

2х+y= - 4   2*(6+1.5y)+y=-4                        x=6+1.5y

                   12+3y+y=-4                                  x=6+1.5*(-4)

                          4y=-16                                    x=6-6

                           y=-4                                       x=0

подставим  y в первое уравнение